PERANCANGAN SISTEM INFORMASI INVENTORI LABORATORIUM PADA LABORATORIUM JURUSAN TEKNIK ELEKTRO - Jumadi Jumadi; lalu A. Syamsul Irfan Akbar; Suthami Ariessaputra (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING AND INFORMATION TECHNOLOGY), 2023)
Inventory management is a very important aspect of the digital era. In the education sector, especially tertiary institutions with laboratories, goods inventory is crucial in asset management. The electrical engineering department has six educational laboratories, requiring a website to inventory tools and materials in each laboratory. The website utilized CodeIgniter and the MVC Model View Controller concept as a basis for building the application. This stage includes making software broken down into small classes, which will later be combined in the next stage and tested with black box testing. The laboratory inventory information system for the Department of Electrical Engineering that was built can provide information in the form of reports the form of suppliers, types of goods, condition of laboratory goods, and their status. In addition, technicians can make reports on laboratory inventory conditions by year and be displayed in graphical form.